P-001 L-arginine ameliorates maternal and pre-pubertal codeine exposure-induced dysregulation of testicular cytoprotective and spermatogenic genes and improves steroidogenesis in adult rat offspring. (30th June 2022) - Akhigbe, R; Ajayi, A
Abstract: Study question: Will maternal exposure to codeine cause transgenerational effect on testicular function and what role will pre-pubertal codeine-exposure and L-arginine treatment play? Summary answer: L-arginine treatment blunted maternal and pre-pubertal codeine exposure-induced downregulation of testicular cytoprotective and spermatogenic genes and distortion of steroidogenesis. What is known already: Codeine, a common drug of abuse, has been reported to impair male infertility by eliciting testicular and sperm damage via oxidative stress-sensitive pathway. On the other hand, L-arginine has been shown to improve testicular perfusion and testicular redox state, thus enhancing male reproductive function. However, no study has evaluated the effect of maternal codeine exposure and concurrent pre-pubertal codeine and L-arginine administration on male reproductive health viz a viz testicular steroidogenesis, spermatogenesis, and sperm quality. Study design, size, duration: This is a prospective experimental study using animal model. Forty pre-pubertal female Wistar rats of comparable age and weight were used for the study. The study lasted two generations. Participants/materials, setting, methods: Forty pre-pubertal female Wistar rats were randomized into vehicle-treated or codeine-treated. After 8 weeks of administration via gavage, animals were paired with stud male Wistar rats (1: 1). Administration continued throughout pregnancy and lactation. Male offsprings were weaned at post-natal day (PND) 21 and each cohort was randomized into vehicle treated, codeine-treated, L-arginine-treated, and codeine with L-arginine-treated. Offspring intervention commenced at PND 28 and lasted for 8 weeks. Main results and the role of chance: Maternal codeine exposure caused increased testicular lactate dehydrogenase activity, concentrations of lactate and uric acid, and reduced testicular sorbitol dehydrogenase activity. In addition, maternal codeine exposure reduced testicular activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and glutathione and Nrf2 concentrations, but increased testicular concentrations of malondialdehyde, 8OHdG, TNF-α, IL-1β, and NFkB, MPO and caspase 3 activities, and DNA fragmentation. Furthermore, codeine exposure reduced steroidogenic markers (3β-HSD, 17β-HSD, FSH, LH, and testosterone), indices of spermatogenesis, and sperm quality. This was associated with reduced expression of regulatory genes for spermatogenesis (mRNA of Ndrg4, Kit, Rhcg, Lrrc34, and Lgals1), and cytoprotection (mRNA SOD, mRNA GPx, and mRNA Nrf2), and increased mRNA TNF-α, mRNA NFkB, and mRNA caspase 3. The observed codeine-induced perturbations were worsened by pre-pubertal codeine exposure in offsprings damned by mothers with codeine exposure but blunted by L-arginine treatment. Limitations, reasons for caution: This study is an animal model; therefore, findings should be extrapolated to human with care. Thus, human studies are recommended. Wider implications of the findings: This study demonstrates for the first time the transgenerational effect of maternal codeine exposure, and the impact of concomitant pre-pubertal codeine use and L-arginine treatment. The present findings add to the available literature by providing further molecular mechanisms through which codeine impairs male reproductive function. Trial registration number: not applicable